2020
DOI: 10.1111/jtxs.12513
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of myofibrillar protein gel strength of Scomberomorus niphonius by riboflavin under UVA irradiation

Abstract: In this study, effects of different concentrations of riboflavin (0, 0.02, and 0.1 μmol/g protein) on myofibrillar protein (MP, Scomberomorus niphonius) gel were characterized. The gel structure and properties were studied with or without Ultraviolet A (UVA) irradiation. Electron spin resonance results showed that riboflavin produced ·OH under UVA irradiation, which subsequently oxidized the MP. Compared with the control group, the addition of riboflavin with UVA irradiation increased the strength of the MP ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…SDS‐PAGE was used to evaluate the crosslinking patterns of proteins in the MP gel samples as described by He et al 23 . An amount of 20 μg of sample was applied to a gel consisting of 5% concentrating gel and 10% separating gel.…”
Section: Methodsmentioning
confidence: 99%
“…SDS‐PAGE was used to evaluate the crosslinking patterns of proteins in the MP gel samples as described by He et al 23 . An amount of 20 μg of sample was applied to a gel consisting of 5% concentrating gel and 10% separating gel.…”
Section: Methodsmentioning
confidence: 99%
“…UV irradiation might also expedite the autooxidation of myoglobin to metmyoglobin in surimi to generate browning (Buamard and Benjakul 2019). Nevertheless, compared with the sharp decline of whiteness in surimi gel incorporating polyphenols and riboflavin received UV irradiation reported by He et al ., (2020b) and Jiang et al ., (2020), whiteness change in our study is negligible.…”
Section: Resultsmentioning
confidence: 96%
“…During the heating process, the hydrogen bonds and hydrophobic interactions that maintained the helical structure were destroyed, which promoted the α‐helix construction to continue unfolding and transforming to other forms (Li et al ., 2020c). In addition, some studies suggested that the rise of β‐sheets content provided favourable conditions for the irreversible aggregation of myosin and the formation of a stable gel network (He et al ., 2020b). By contrast, the content of α‐helix in the M‐YG group was lower than that in the M group.…”
Section: Resultsmentioning
confidence: 99%
“…Spanish mackerel ( Scomberomorus niphonius ), with a higher yield in China, is an alternative resource that has attracted more attention. However, prepared surimi has a limited flavour and gel quality because of the significant proportion of red meat in its muscles (He et al ., 2020b). Therefore, it is important to find methods to improve the quality of such surimi.…”
Section: Introductionmentioning
confidence: 99%